Guía para la concesión de licencias obligatorias y uso gubernamental de patentes farmacéuticas - Carlos María Correa (South Centre, 2020)
Al igual que otros derechos, los derechos de patente no son absolutos. Hay situaciones en las que su ejercicio puede limitarse para proteger los intereses públicos. Esas situaciones pueden surgir, por ejemplo, cuando debe garantizarse el acceso a los productos farmacéuticos necesarios. Las licencias obligatorias y el uso gubernamental con fines no comerciales son instrumentos, previstos en la mayoría de las leyes de todo el mundo, que pueden utilizarse específicamente para atender las necesidades de salud pública. El presente documento tiene por objeto proporcionar orientación jurídica para el uso eficaz de esos instrumentos, de conformidad con el derecho internacional. – – Like other rights, patent rights are not absolute. There are situations in which their exercise can be limited to protect public interests. Such situations may arise, for instance, when access to needed pharmaceutical products must be ensured. Compulsory licenses and government use for non-commercial purposes are tools, provided for under most laws worldwide, that can specifically be used to address public health needs. This document is intended to provide legal guidance for the effective use of such tools, consistently with the international law.
Keywords: 300; Access to Medicines; Affordable Medicines; Compulsory Licenses; COVID-19; Data Exclusivity; Diagnostics; Doha Declaration on the TRIPS Agreement and Public Health; Evergreening; Flexibilities; Global Health; Government Use; Health; Innovation; Intellectual Property; Least Developed Countries (LDCs); Patent; Pharmaceuticals; Public Health; Research and Development (R&D); TRIPS; Vaccines; Voluntary License; WHO; WHO Global Strategy (GSPOA); World Health Organization (WHO)